A global map of human pressures on tropical coral reefs. Issue 1 (28th December 2021) - Andrello, Marco; Darling, Emily S.; Wenger, Amelia; Suárez‐Castro, Andrés F.; Gelfand, Sharla; Ahmadia, Gabby N.
Abstract: As human activities on the world's oceans intensify, mapping human pressure is essential to develop appropriate conservation strategies and prioritize investments with limited resources. Here, we map six human (nonclimatic) pressures on coral reefs using the latest quantitative data on fishing, water pollution (nitrogen and sediments), coastal population, industrial development, and tourism. Using a percentile approach to rank different stressors, we identify the top‐ranked local pressure and estimate a cumulative pressure index for 54, 596 global coral reef pixels at 0.05° (∼5 km) resolution. We find that coral reefs are exposed to multiple intense local pressures: fishing and water pollution (nutrients and sediments) are the most common top‐ranked pressures worldwide (in 30.8% and 32.3% of reef cells, respectively), although each pressure was ranked as a top pressure in some locations. We also find that local pressures are similar inside and outside a proposed global portfolio of coral reef climate refugia, suggesting that even potential climate refugia have high levels of local human pressure that require effective management. Our findings and datasets provide the best available information that can ensure local pressures are effectively managed across the world's coral reefs.